2020
DOI: 10.1136/bmjoq-2019-000723
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of clinical coding and payments through student doctor–coder collaboration in a tertiary haematology department

Abstract: Hospitals within the UK are paid for services provided by ‘Payment-by-Results’. In a system that rewards productivity, effective collaboration between coders and clinicians is crucial. However, clinical coding is frequently error prone and has been shown to impact negatively on departmental revenue. Our aim was to increase the median number of diagnostic codes per sickle cell inpatient admission at Guy’s Hospital by 3. Three interventions were implemented using the Plan, Do, Study, Act structure. This consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Furthermore, due to their legal value, especially as more litigation claims are increasing on annual basis among surgical departments [ 26 ], administrations of concerned bodies often push for more documentation at the expense of proper healthcare delivery [ 25 ]. Moreover, proper documentation is essential as it is a cornerstone in the quality development of hospital services and long-term patient-oriented treatment plans and influences revenue [ 27 ]. Nevertheless, the value of documentation throughout healthcare is understudied, as there are no significant efforts delineating the impact of proper documentation on patient care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to their legal value, especially as more litigation claims are increasing on annual basis among surgical departments [ 26 ], administrations of concerned bodies often push for more documentation at the expense of proper healthcare delivery [ 25 ]. Moreover, proper documentation is essential as it is a cornerstone in the quality development of hospital services and long-term patient-oriented treatment plans and influences revenue [ 27 ]. Nevertheless, the value of documentation throughout healthcare is understudied, as there are no significant efforts delineating the impact of proper documentation on patient care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An explanation may be that hospital coding did not completely document relevant comorbidities for these patients. Evidence of incomplete capture of comorbidities using hospital admission and discharge coding data has been documented by other authors throughout the world [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assure the accuracy of clinical documentation, the proposed interprofessional collaborative educational sessions, which are in place in some health services were reported to be beneficial. Previous studies also reported that improved clinician-coder collaboration is beneficial ( 30 ) as it can improve the quality of coding ( 47 ).…”
Section: Discussionmentioning
confidence: 99%